How I live now - Rosoff, Meg, 1956- (New York : Wendy Lamb Books, 2006)
To get away from her pregnant stepmother in New York City, fifteen-year-old Daisy goes to England to stay with her aunt and cousins, with whom she instantly bonds, but soon war breaks out and rips apart the family while devastating the land. "Every war has turning points and every person too." Fifteen-year-old Daisy is sent from Manhattan to England to visit her aunt and cousins she's never met: three boys near her age, and their little sister. Her aunt goes away on business soon after Daisy arrives. The next day bombs go off as London is attacked and occupied by an unnamed enemy. As power fails, and systems fail, the farm becomes more isolated. Despite the war, it's a kind of Eden, with no adults in charge and no rules, a place where Daisy's uncanny bond with her cousins grows into something rare and extraordinary. But the war is everywhere, and Daisy and her cousins must lead each other into a world that is unknown in the scariest, most elemental way. A riveting and astonishing story.
Keywords: War stories; Cousins -- Fiction; Families -- England -- Fiction; Farm life -- England -- Fiction; Eating disorders -- Fiction; Young adult fiction; Printz Medal; England -- Fiction